The scaling up of a failed war and its dangers - Urcuyo, Constantino (2012)
Until recently, the War on Drugs had been confined to Colombia and had then spread to Mexico. However, in both cases, this war has not been able to proclaim victory. Both Colombia and Mexico have made unsuccessful efforts to fight against this war, making it possible to qualify it as a failed war. This paper, after analyzing the dimensions of the War on Drugs, will address the extension of the war to the Central American scenario, along with the possible negative implications for democracy, concluding the analysis with a review of the initiatives of Merida and the Central American Regional Security Initiative, as well as the structure devised by the U.S. Southern Command for their execution.